PENELITIAN TINDAKAN KELAS BAGI GURU AGAMA HINDU - Ida Ayu Made Pradnyawati (Guna Widya: Jurnal Pendidikan Hindu, 2021)
Classroom action research is a study that raises the actual problems faced by teachers in the classroom. Several previous research results indicate a positive impact on the implementation of classroom action research on improving the quality of learning in the classroom. Teachers in general, including Hindu religion teachers, are important to carry out classroom action research to improve the quality of learning in the classroom. Before carrying out classroom action research, you should first understand the meaning, benefits, and limitations of classroom action research. Then follow the classroom action research steps carefully. The classroom action research steps discussed in this paper are: (1) developing a focus problem; (2) planning improvements / alternative actions; (3) carry out and observe actions; (4) compile a class action research report; (5) dissemination of classroom action research results.